Analisis Karakteristik Konseptual Hutang dan ekuitas dalam struktur Pembiayaan Perusahaan - Sarah Della Rama Dhani; Siti Fadia Adha; Nisa Saffanah Auliandari; Kayla Dwi Nur Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the conceptual characteristics of liabilities (debt) and equity (Capital), as well as to examine their relationship within a company’s financing structure. The research employs a descriptive qualitative approach through a literature review method without conducting field research. Liabilities and equity are two fundamental elements of a company’s financing structure that play a crucial role in the preparation of financial statements. The study is based on an extensive review of relevant literature, accounting standards, and theoretical frameworks related to liabilities and equity. The findings indicate that liabilities represent obligations arising from past transactions that must be settled through the sacrifice of economic resources in the future. In contrast, equity represents the residual interest in a company’s assets after deducting all liabilities. A proper understanding of these two concepts is essential for the preparation of reliable and relevant financial statements that meet the information needs of stakeholders.